Alleviation of Adipose Tissue Inflammation and Obesity Suppression by a Probiotic Strain That Induces GLP-1 Secretion - A-Ram Kim; Seong-Gak Jeon; So-Jung Park; Heeji Hong; Byung Kwon Kim; Hyung-Ran Kim; Chun-Pyo Hong; Bo-Gie Yang (Microorganisms)
Glucagon-like peptide-1 (GLP-1) is a hormone secreted from enteroendocrine cells that can promote weight loss and blood glucose improvement. We screened probiotic strains that effectively stimulate GLP-1 secretion from human enteroendocrine cells and then investigated the efficacy of this strain in a high-fat diet (HFD)-induced mouse model of obesity. Lactiplantibacillus plantarum GB104 greatly induced GLP-1 secretion by increasing expression of the proglucagon gene (GCG), but not the proprotein convertase subtilisin/kexin type 1 gene (PCSK1) in the human enteroendocrine cell line NCI-H716. In an HFD-induced mouse model of obesity, GB104 inhibited weight gain and improved blood glucose levels by increasing blood GLP-1 levels. It also tended to attenuate the HFD-induced changes in blood levels of other hormones and suppressed fat accumulation in the liver and adipose tissues. In white adipose tissue, GB104 suppressed inflammation by reducing pro-inflammatory M1 macrophages and increasing anti-inflammatory M2 macrophages and regulatory T cells. Probiotic strains that promote GLP-1 secretion, such as GB104, may serve as a promising candidate for dietary intervention against obesity and metabolic diseases.